The impact of emotional appeals (guilt and pride) and product involvement in green advertising on consumer attitude and purchase intention - Zhou, Aili (2020)
The study was designed to investigate the effects of emotional appeals (guilt vs. pride) in green advertising and the level of product involvement (high vs. low) on individuals’ attitudes toward ad, attitudes toward brands and purchase intentions. Specifically, it intended to determine the more effective emotional appeal under different product involvement levels. In the survey, a zero-emission vehicle was selected as a high involvement product and Fair Trade coffee as a low involvement product. Based on the success of the pilot test, the formal experiment was conducted. The results revealed that although the differences are not significant, customers develop more favourable ad attitudes, brand attitudes and purchase intentions when green ads exhibited guilt appeal rather than pride appeal in the case of high involvement products. Concerning low involvement products, the effects of guilt appeal are significantly better than that of pride appeal in influencing customers' attitudes and purchase intentions. Furthermore, displaying guilt appeal in the green ads of low involvement products is more effective than in those of high involvement products. Hence, starting from the research findings, the relevant implications revealed will provide some valuable guidance for green enterprises. In addition, the limitations of the methodology and future directions were also discussed in the end.